A dynamic anisotropic Spatially-Averaged Two-Fluid Model for moderately dense gas-particle flows. (May 2020) - Rauchenzauner, Stefanie; Schneiderbauer, Simon
Highlights: An anisotropic turbulence model for moderately dense gas-particle flows. Anisotropic closure models for the Reynolds-stresses are applied. Closure models for the individual components of the drift velocity are derived. Dynamic adjustment of the correlation coefficients in coarse-grid simulations. An a priori validation shows good agreement with highly resolved simulation data. Abstract: We present an anisotropic, dynamic multi-phase turbulence model for moderately dense gas-particle flows by spatially averaging the kinetic-theory based two-fluid model (Schneiderbauer, AIChE J., 2017; 63(8): 3544–3562). The filtered gas-particle drag force can be approximated by the resolved drag force corrected by the drift velocity (Parmentier et al., AIChE J., 2012; 58(4): 1084–1098). The drift velocity can be expressed as a correlation between the gas-phase velocity and the solid volume fraction. We propose to calculate the correlation coefficients locally and dynamically by application of a scale-similarity approach. Therefore, we show that test-filters can be employed to estimate the correlation coefficients in coarse-grid simulations. Furthermore, transport equations for the components of the highly anisotropic Reynolds-stress tensor are derived, and closure models known from single-phase LES modelling are applied to the unresolved terms with the exception of the interfacial work term, which is expressed by the correlations between the velocities of the phases. In addition, the cluster-induced turbulence production term (Capecelatro et al., J. Fluid Mech., 2015; 780: 578–635) arising in the gas-phase Reynolds-stress transport equation is closed using the drift velocity. An a priori validation of the developed closure models against filtered fine-grid simulation data of unbound fluidization for Geldart type A and B particles, as well as an a posteriori verification in wall-bounded fluidized beds of Geldart type A and B particles are conducted.